Systemic Antisense Therapeutics for Dystrophin and Myostatin Exon Splice Modulation Improve Muscle Pathology of Adult mdx Mice - Ngoc Lu-Nguyen; Alberto Malerba; Linda Popplewell; Fred Schnell; Gunnar Hanson; George Dickson (Elsevier, 2017)
Antisense-mediated exon skipping is a promising approach for the treatment of Duchenne muscular dystrophy (DMD), a rare life-threatening genetic disease due to dystrophin deficiency. Such an approach can restore the disrupted reading frame of dystrophin pre-mRNA, generating a truncated form of the protein. Alternatively, antisense therapy can be used to induce destructive exon skipping of myostatin pre-mRNA, knocking down myostatin expression to enhance muscle strength and reduce fibrosis. We have reported previously that intramuscular or intraperitoneal antisense administration inducing dual exon skipping of dystrophin and myostatin pre-mRNAs was beneficial in mdx mice, a mouse model of DMD, although therapeutic effects were muscle type restricted, possibly due to the delivery routes used. Here, following systemic intravascular antisense treatment, muscle strength and body activity of treated adult mdx mice increased to the levels of healthy controls. Importantly, hallmarks of muscular dystrophy were greatly improved in mice receiving the combined exon-skipping therapy, as compared to those receiving dystrophin antisense therapy alone. Our results support the translation of antisense therapy for dystrophin restoration and myostatin inhibition into the clinical setting for DMD. Keywords: antisense oligonucleotides, Duchenne muscular dystrophy, dystrophin, exon skipping, myostatin